Improvement of resistance to fusarium root rot through gene pyramiding and validation of SSR PVBR87 marker in common bean - Obala, Jimmy (2011)
Fusarium root rot caused by Fusarium solani f. sp. phaseoli is among the most serious diseases of the common bean in Uganda causing total crop loss in susceptible cultivars. Studies have indicated that 2-9 genes located at different loci govern resistance to Fusarium root rot among different resistance sources. Accumulation of several of these genes from the different sources into a single genetic background has been proposed to result in an increased level of resistance to Fusarium root rot, and more effective transfer of this resistance into consumer-preferred cultivars. Use of molecular markers together with phenotypic selection could speed up breeding progress for Fusarium root rot resistance. A simple sequence repeat (SSR) PVBR87 marker linked to Fusarium root rot resistance quantitative trait loci (QTL) was identified in a previous study but its use in identifying resistant genotypes outside the original two mapping populations has not been determined. This study estimated the number of pyramided Fusarium root rot resistance genes from four sources of resistance, their interaction and effectiveness in improving Fusarium root rot resistance levels. The study also validated the association of the SSR PVBR87 marker with resistance to Fusarium root rot in an additional population. The study was conducted at the International Centre for Tropical Agriculture (CIAT) based at the National Agricultural Research Laboratories – Kawanda, Uganda. Four Fusarium root rot resistant (R) inbred lines: MLB-48-89A (48), MLB-49-89A (49), G2333 (G2) and G685 (G6), and two susceptible (S) lines: K20 and Kanyebwa (Kan) were used in the study. A double cross (DC) was developed from the four resistant parents. The DC F1 and each resistant parent were crossed to the two susceptible cultivars to form five-parent crosses and single crosses, respectively. Parental, F1 and F2 populations were subjected to Fusarium solani f. sp. phasoeli isolate-3. Twenty one days xi after planting, symptom severity was assessed on a scale of 1-9 (varied at 1,2,3,4,5,6,7,8,9). Plants of each cross were grouped into resistant (score 1-4) and susceptible (score 5-9). F2 plants of K20 x G2 and 49 x Kan were screened with SSR PVBR87 marker. The estimated number of genes and gene interactions were determined using X2 goodness-of-fit test (P = 0.05) and means were compared by “Students t-test” (P = 0.05). The association of SSR PVBR87 marker to Fusarium root rot resistance was determined using X2 test of independence and single marker regression analysis (P = 0.05). Two to three genes segregated in the R x R single crosses and at least four genes segregated in the double cross population indicating three of the four resistant parents differed from each other by at least one gene and two of the four parents have at least one gene in common. Genetic effects among the crosses included additive and dominance effects and epistatic interactions. Five-parent crosses performed better than the single crosses, demonstrating the potential of using combined resistance in improving resistance to Fusarium root rot in susceptible bean cultivars. The SSR PVBR87 marker showed significant association to Fusarium root rot resistance in both K20 x G2 and Kan x 49 indicating its stability in different genetic background but still requires further validation in different environments and in additional genetic backgrounds to determine its use for marker-assisted breeding for improving resistance to Fusarium root rot. The genes responsible for the higher levels of Fusarium root rot resistance in the pyramids are not specifically known. It is necessary that these resistance genes be tagged with molecular markers. Tagging of the genes with molecular markers would provide knowledge of their genomic locations, the nature of their interactions and also facilitate the transfer of these genes or alleles, through molecular marker-assisted gene introgression, into other agronomically superior, but Fusarium root rot susceptible cultivars. Since no selection for Fusarium root rot resistance or any other desirable agronomic traits was practiced in this study, there is need to select between and within families from among the five-parent cross populations and the single crosses for resistance to Fusarium root rot. However, the predominance of non-additive gene effects for Fusarium root rot resistance, especially in the five-parent crosses suggests that selection for resistance would be more effective at advanced generations of selfing. The bean parents used in constructing the five-parent cross populations are of diverse seed character, growth habit, maturity period, and have varied response to several abiotic and biotic constraints. There is also need to select for these traits in the populations developed in this study as these traits eventually affect acceptability of any potential new variety. The amounts of phenotypic variation explained by the SSR PVBR87 in two populations were low; hence, there is still need to further validate the marker in additional populations and in several environments to determine its efficacy for marker-assisted breeding for Fusarium root rot resistance.